Endogenous and exogenous testosterone and the risk of prostate cancer and increased prostate‐specific antigen (PSA) level: a meta‐analysis. (24th February 2016) - Boyle, Peter; Koechlin, Alice; Bota, Maria; d'Onofrio, Alberto; Zaridze, David G.; Perrin, Paul; Fitzpatrick, John; Burnett, Arthur L.; Boniol, Mathieu
Abstract : Objective: To review and quantify the association between endogenous and exogenous testosterone and prostate‐specific antigen (PSA) and prostate cancer. Methods: Literature searches were performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Prospective cohort studies that reported data on the associations between endogenous testosterone and prostate cancer, and placebo‐controlled randomized trials of testosterone replacement therapy (TRT) that reported data on PSA and/or prostate cancer cases were retained. Meta‐analyses were performed using random‐effects models, with tests for publication bias and heterogeneity. Results: Twenty estimates were included in a meta‐analysis, which produced a summary relative risk (SRR) of prostate cancer for an increase of 5 nmol/L of testosterone of 0.99 (95% confidence interval [CI] 0.96, 1.02) without heterogeneity ( I ² = 0%). Based on 26 trials, the overall difference in PSA levels after onset of use of TRT was 0.10 ng/mL (−0.28, 0.48). Results were similar when conducting heterogeneity analyses by mode of administration, region, age at baseline, baseline testosterone, trial duration, type of patients and type of TRT. The SRR of prostate cancer as an adverse effect from 11 TRT trials was 0.87 (95% CI 0.30; 2.50). Results were consistent across studies. Conclusions: Prostate cancer appears to be unrelated to endogenous testosterone levels. TRT for symptomatic hypogonadism does not appear to increase PSA levels nor the risk of prostate cancer development. The current data are reassuring, although some caution is essential until multiple studies with longer follow‐up are available.